Efektywność health coachingu w dobie pandemii = The Efficiency of Health Coaching in the Pandemic Times - Konstańczak, Stefan (1955- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In his article, the author made an attempt to highlight the genesis and specificity of health coaching which has been dynamically developing recently. The author`s initial assumption is to consider health coaching as a set of impacts stimulating pro-health behaviors of clients. The motivational interviewing procedure is a tool enabling effective interaction of this type.
Keywords: coaching; health coaching; dialog motywacyjny; pandemia; efektywność coachingu; motivational interviewing; pandemic; efficiency of health coaching